Direct tissue-sensing reprograms TLR4+ Tfh-like cells inflammatory profile in the joints of rheumatoid arthritis patients - Amaral-Silva, Daniela (2021)
Funding Information: We thank Cláudia Andrade for technical support and Juliana Gonçalves for testing samples for SARS-CoV-2 exposure. We are extremely grateful to all the participants of the study and to the whole rheumatology department at Hospital Egas Moniz that made this study possible. This work was supported by Fundação para a Ciência e Tecnologia (FCT) PTDC/MEC-REU/29520/2017, by iNOVA4Health UID/Multi/04462 and by Portuguese Society for Rheumatology (SPR) grants to H.S. H.S. is supported by FCT through IF/01722/2013 and CEECIND/01049/2020, DAS and RCT were supported by FCT through PD/BD/137409/2018 and UID/Multi/04462, respectively. Publisher Copyright: © 2021, The Author(s).